2010
DOI: 10.1111/j.1365-2605.2009.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mouse models of diabetes mellitus in studies of male reproduction

Abstract: Diabetes Mellitus (DM) has been found to have subtle yet profound effects on the metabolic status of the testis, the expression of numerous spermatogenic genes and is associated with increased numbers of sperm with nuclear DNA damage. The precise mechanism causing these detrimental effects remains unknown. The presence of increased levels of the most prominent member (carboxymethyllysine - CML) of the advanced glycation end product adducts and their receptor (RAGE) in the reproductive tract of DM men has provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
1
22
1
1
Order By: Relevance
“…Several attempts have been made in recent years to establish a good animal model like Ins 2 Akita mouse and animals fed with high-fat diet [24,25] which do not involve any pharmacological intervention. These approaches may provide a new and exciting model to study the pathophysiological changes associated with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made in recent years to establish a good animal model like Ins 2 Akita mouse and animals fed with high-fat diet [24,25] which do not involve any pharmacological intervention. These approaches may provide a new and exciting model to study the pathophysiological changes associated with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is known to play an important role in various manifestations of MetS, but one that is thought to be only an early event in the pathology of what are chronic diseases (Roberts & Sindhu 2009). In diabetes, there is evidence both in men and in animal models, whether spontaneously occurring (O'Neill et al 2009) or chemically induced diabetic mice (Shrilatha & Muralidhara 2007a, O'Neill et al 2009) and rats (Shrilatha & Muralidhara 2007b), that the condition is associated with marked increases in oxidative stress and sperm nDNA damage. Hyperglycaemia is known to cause oxidative stress (Wautier & Schmidt 2004, Chekir et al 2006 and to accelerate the accumulation of advanced glycation end products and their receptor RAGE, both of which are capable of generating, promoting and/or amplifying oxidative stress and its detrimental consequences.…”
Section: Discussionmentioning
confidence: 99%
“…We identified high levels of N 3 -carboxymethyl-lysine (CML), the most prominent advanced glycation end product (AGE; Mallidis et al 2009) and its receptor (RAGE; Mallidis et al 2007) in the testis, epididymis and sperm of diabetic men and mouse models alike (O'Neill et al 2009). As this group of compounds is known to cause cellular dysfunction, oxidative stress and DNA damage in various organs and in a variety of conditions (Vlassara & Palace 2002), we hypothesise that they may also play an equally destructive role in the reproductive tract of diabetics and MetS patients and as such contribute to the sperm nDNA fragmentation seen in these men.…”
Section: Introductionmentioning
confidence: 99%
“…14,21,22 Diabetes also induces DNA damage 36 and the formation of advanced glycation end products and their receptors. 18,37 These adverse effects of diabetes may have significance as regards to the fertility outcome. 9 In our study, we showed an increase in mitochondrial oxidative DNA damage in DM1 and predominantly nuclear oxidative DNA damage in DM3.…”
Section: Discussionmentioning
confidence: 99%
“…9 Further, the increase in DNA damage, in sperm and reproductive tract epithelial cells of diabetic men and animal models correlates with high levels of advanced glycation end products and their receptors. 17,18 A microarray analysis of spermatozoa collected from diabetic men showed the differential expression of 285 genes. Among them, 21 genes were mainly related to sperm structure and function, DNA replication and repair, transcription, and intracellular signaling.…”
Section: Introductionmentioning
confidence: 99%